PEMANFAATAN BENDA KONKRIT DALAM PEMBELAJARAN MATEMATIKA DASAR DI PULAU NUSALAUT - Pattimukay, Nessy (PAKEM : Jurnal Pengabdian Kepada Masyarakat, 2025)
Mathematics is one of the sciences that plays an important role in human life. Therefore, mathematics is taught in elementary school, middle school, and college. Not a few students have difficulty understanding basic mathematical concepts. Therefore, teachers need to be creative in preparing learning media that support learning and make it easier for students to understand the concepts taught. Therefore, this community service activity is more directed at teaching assistance activities. This activity was carried out in several elementary schools on the island of Nusa Laut. The schools involved in the teaching assistance activities for mathematics subjects were State Elementary Schools 168 and 35, Central Maluku. The teaching assistance team, especially for mathematics subjects, prepares the materials needed for the activity, including LKPD (Student Activity Sheets), teaching materials, and demonstration tools. Based on the results of students' work on LKPD, student performance during presentations, and the results of feedback, it was found that most students had understood the material taught, and students were also happy with the learning that had been done